2010
DOI: 10.1086/648731
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Infection with West Nile Virus Years after Initial Infection

Abstract: West Nile virus (WNV) RNA was demonstrated in 5 of 25 (20%) urine samples collected from convalescent patients 573 to 2,452 days (1.6 to 6.7 years) after WNV infection. Four of the 5 amplicons sequenced showed >99% homology to the WNV NY99 strain. These findings show that individuals with chronic symptoms following WNV infection may have persistent renal infection over several years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
165
0
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(175 citation statements)
references
References 12 publications
4
165
0
6
Order By: Relevance
“…The purpose of this study was to explore the potential effect of synonymous codon usage bias in the beginning region of WNV and the tRNA concentrations for this region in the vector and dead-end host. Our observations indicated that some patients were persistently infected with WNV and that the kidney may be a preferred site of continued replication and source of shedding (Murray et al, 2010a), suggesting that codon usage in this virus may be influenced by its dead-end host. The significant increase in translation rate owing to the appropriate arrangement of codons has an important impact on how the translation machinery functions.…”
Section: Discussionmentioning
confidence: 77%
“…The purpose of this study was to explore the potential effect of synonymous codon usage bias in the beginning region of WNV and the tRNA concentrations for this region in the vector and dead-end host. Our observations indicated that some patients were persistently infected with WNV and that the kidney may be a preferred site of continued replication and source of shedding (Murray et al, 2010a), suggesting that codon usage in this virus may be influenced by its dead-end host. The significant increase in translation rate owing to the appropriate arrangement of codons has an important impact on how the translation machinery functions.…”
Section: Discussionmentioning
confidence: 77%
“…In contrast to neurons and macrophages, these latter cells do not die following infection. Instead they survive and often become persistently infected (21,22,29). Consistent with these results, we show that in vitro infection of macrophages with either Dengue-2 or Modoc virus results in cell killing similar to that of CPT at 48 hpi, whereas infection with either virus fails to kill renal epithelial cells and fibroblasts (MDCK, 293T, Vero, SW primary MEF, and C57/Bl primary MEF) even when the cells are infected at extremely high titer (m.o.i.…”
Section: Discussionmentioning
confidence: 99%
“…Further, the large increase in the incidence of cases of WNV in North America registered in 2012 makes the possibility of further geographical expansion of the infection in Europe highly likely, under the influence of an expansion of the boundaries of competent vectors. Considering the possibility of chronic and persistent human infections (Murray et al, 2010) and the evidence of serious long-term sequelae in patients with a history of WNV infection (Nolan et al, 2012), it becomes apparent that WNV infection could have substantial public-health implications and emphasizes the importance of having surveillance systems monitoring the activity of WNV in humans, mosquitoes, birds and other animals.…”
mentioning
confidence: 99%